A Shifted-Inverse Adaptive Multigrid Method for the Elastic Eigenvalue Problem (Communications in Computational Physics, 2020)
A shifted-inverse iteration is proposed for the finite element discretizationof the elastic eigenvalue problem. The method integrates the multigrid scheme andadaptive algorithm to achieve high efficiency and accuracy. Error estimates and optimal convergence for the proposed method are proved. Numerical examples show thatthe proposed method inherits the advantages of both ingredients and can compute lowregularity eigenfunctions effectively.